Adolescents’ Perceptions of Physical Development Relative to Peers and Antisocial Behaviors - Dalzell, Erica L. (Journal of developmental and life-course criminology, 2021)
Two features of adolescence have remained largely constant over time—(1) youth experience drastic physical changes during puberty, and (2) many youth engage in antisocial or delinquent behavior. Prior work has found a positive relation between off-time pubertal timing and a host of adverse behaviors including reduced academic performance and substance use (Simmons 2017; Westling et al. Journal of Adolescent Health, 42(6), 555−563, 2008). However, previous research is largely limited in its measurement of pubertal timing in that it does not account for youth perceptions of self, social comparisons, and peer influence—salient components of the developmental period. The present study addressed this limitation by testing the effect of self-perceived development on antisocial behavior. Among a nationally representative sample of 4803 youth, the present study examined the effect of a self-report, peer-relevant measure of physical development on antisocial behaviors, varying in severity. Results revealed a positive relation between youths’ perceived physical development relative to same-aged peers and five categories of behaviors: antisocial behaviors, non-violent offending, violent offending, substance use, and weapon use. Overall, when youth reported being more physically developed than their same-aged peers, they were more likely to engage in deviant behavior. The results provide evidence for including self-report, peer-relevant measures of physical maturity from the youth perspective when studying adolescence and undesirable youth behavior.